Productive and nutritional performance of forage sorghum intercropped with soybean according to nitrogen doses - Fidelis, Rodrigo Ribeiro; Gonzaga, Luiz Antonio Menezes; Silva, Rubens Ribeiro da; Andrade, Carlos Augusto Oliveira de (Comunicata Scientiae, 2016)
The objective of this study was to evaluate the nutritional and productive performance of forage sorghum in an intercropping with soybean submitted to nitrogen doses. The experiment was in blocks with a complete randomized design, with four repetitions in a factorial arrangement (6x2+1), with six doses of nitrogen (0, 20, 40, 60, 80 e 100 kg de N ha-1), in two systems, being the intercropping of sorghum x soybean and one control with only sorghum with an application of 100 kg de N ha-1. The variables studied were sorghum dry and fresh matter productivity, crude protein of sorghum, fresh matter productivity for the intercropping and protein efficiency index. Higher doses of N applied as cover on the sorghum x soybean intercropping increased the quality and the productivity of the forage, when compared to the monoculture. The sorghum intercropping with two lines of soybean provides higher productivities of fresh matter, dry matter and crude protein. The intercropping with one and two lines of soybean provides a saving of 40% and 60%, respectively, of nitrogen on the production of crude protein when compared to monoculture.